Martensitic transformation in as-grown and annealed near-stoichiometric epitaxial Ni2MnGa thin films - Machain, P. (2015)
Fil: Machain, P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina